Strategies for enhancing enrollment in one registered nurse-bachelor of science in nursing program. - Williams SJ (Teaching & Learning in Nursing, 2008)
Associate degree and diploma graduates make up the largest number of registered nurses (RNs) in today's workforce, and only 16% return to school for a baccalaureate degree. The nursing shortage and the rapid expanding changes in the delivery of health care have created the demand for more nurses prepared at an educational level appropriate for the responsibilities required of them as professional nurses. Cost-effective and flexible RNDSbachelor of science in nursing (BSN) programs are necessary to meet this need.